A Comparison of Patient Safety Competencies between Clinical and Classroom Settings among Nursing Students - Amilia, Rizqi; Nurmalia, Devi (Nurse Media Journal of Nursing, 2020)
Background: As nurses play an important role in the implementation of patient safety in hospitals, competencies of patient safety should be developed and enhanced among nursing students. Self-assessment is a method that can be used to assess patient safety and its dimensions to help the students prepare themselves before entering the work life.Purpose: This study aimed to investigate differences in patient safety competencies between classroom and clinical settings among nursing students using a self-assessment method.Methods: A descriptive study using the Health Professional Education in Patient Safety Survey (H-PEPSS) questionnaire was conducted among 181 nursing students in a public university in Indonesia. Paired t-test, ANOVA, and independent t-test were performed to determine the comparison in the values of patient safety dimensions across classroom, clinical learning, and year of nursing course.Results: Nursing students showed a higher mean value in the classroom setting than the clinical setting. Out of the seven dimensions of patient safety competencies, â€œclinical safetyâ€ (M=4.36) and â€œcommunicate effectivelyâ€ (M=4.29) obtained the highest score in classroom setting, while â€œadverse eventsâ€ showed the lowest (M=4.03). In the clinical setting, â€œclinical safetyâ€ (M=4.19) and â€œcommunicate effectivelyâ€ (M=4.12) obtained the highest score, while â€œworking in teamsâ€ (M=3.82) was the lowest. The third-year students showed a better score than the fourth year in most dimensions.Conclusion: In this study, the patient safety competencies among nursing students were higher in the classroom setting than in the clinical setting. It is recommended to investigate the factors that can increase the achievement of patient safety competence among nursing student in the clinical setting.